2004
DOI: 10.1364/ol.29.001227
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer into mammalian cells by use of a nanosecond pulsed laser-induced stress wave

Abstract: Plasmid DNA has been successfully delivered to mammalian cells by applying a nanosecond pulsed laser-induced stress wave (LISW). Cells exposed to a LISW were selectively transfected with plasmids coding for green fluorescent protein. It was also shown that transient, mild cellular heating (approximately 43 degrees C) was effective in improving the transfection efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 15 publications
0
57
0
Order By: Relevance
“…We consider that this component in adiabatic cooling after switch-off of the laser, decreasing of pressure to about 30%, may have emerged owing to the additional interaction with plasma and shock wave due to complex nonlinear effects, such as the inverse Bremsstrahlung effect and Richtmyer-Meshkov instability [14,15]. Although results that have already been reported were not cleared [1,2], we consider that this component plays an important role in delivering foreign genes into cells effectively without ordinary diffusion. As a conclusion, we consider that stress waves emerging in a confined geometry are highly effective for transferring foreign genes into cells in vitro since the confined geometry has broadband and unidirectional signal that which do not produce a measurable tensile component and may exclude the biological effects induced by cavitation.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…We consider that this component in adiabatic cooling after switch-off of the laser, decreasing of pressure to about 30%, may have emerged owing to the additional interaction with plasma and shock wave due to complex nonlinear effects, such as the inverse Bremsstrahlung effect and Richtmyer-Meshkov instability [14,15]. Although results that have already been reported were not cleared [1,2], we consider that this component plays an important role in delivering foreign genes into cells effectively without ordinary diffusion. As a conclusion, we consider that stress waves emerging in a confined geometry are highly effective for transferring foreign genes into cells in vitro since the confined geometry has broadband and unidirectional signal that which do not produce a measurable tensile component and may exclude the biological effects induced by cavitation.…”
Section: Resultsmentioning
confidence: 78%
“…The generation and dynamics of stress waves formed by a target material of with a direct or confined geometry in Q-switched ns pulse laser irradiation have been focused on as the topic of investigations in medical and biological ultrasonic, clinical and biophysical fields [1][2][3][4]. Mulholland et al have reported the laser-induced stress wave of a polyimide target, as a direct geometry, interacted with an ArF excimer laser (wavelength 193 nm, full width at half maximum: FWHM 29 ns, energy 350 mJ) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Laser induced stress waves (LISWs) are so expected as tool for gene transfection into a cell [1][2][3]. However, as pointed out by A. G. Doukas et al [4] pressure waves caused by laser irradiation interact with tissue, cells, and cellular structures in ways that are not understood deeply.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously applied laser induced stress waves ͑LISWs͒ to gene transfer into rat skin 6 and NIH 3T3 cells. 7 These reports indicated that highly-efficient and site-specific gene transfer can be achieved by this method, and that a LISW can propagate deeply from the surface of the tissue. Polyethylenimine ͑PEI͒ is a synthetic cationic vector and has been shown to be a versatile gene transfer tool in vivo.…”
Section: Introductionmentioning
confidence: 99%